Fatigue Life Prediction of the Pin Coupling with Elastic Sleeves Based on Transient Dynamics and the ARIMA Model - Hu Yuming; Xiong Xin; Guo Kai (Jixie chuandong)
In order to deeply study the influence of parallel misalignment failure on fatigue life of pin couplings with elastic sleeves, on the basis of transient dynamic analysis, the influence of different degrees of parallel misalignment on fatigue life is obtained. Based on transient dynamic fatigue analysis data, combined with the differential autoregressive integrated moving average (ARIMA) model, the fatigue life prediction of pin couplings with elastic sleeves is realized. The results show that the minimum fatigue life of pin couplings with elastic sleeves decreases with the increase of the degree of parallel misalignment, and when the degree of parallel misalignment is less than 2.63%, the decrease of minimum fatigue life increases gradually. The predicted fatigue life of 4.74% parallel misalignment is 1.214 0×106, and the relative error between the predicted value and the simulation value is 0.22%, indicating the reliability of the ARIMA model in predicting fatigue life. The research results can provide guidance for the anti-fatigue optimization design of pin couplings with elastic sleeves.